Contextuality of cognitive control deficits in alcohol dependence — pro et contra - Anna A. Berezin; Anna V. Trusova; Anton N. Gvozdetcki; Svetlana G. Klimanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Cognitive impairment, including cognitive control, mediates the negative social consequences of alcohol-related behavior, but few studies have examined these processes in the Russian speaking population using modern and standardized assessment methods. Thus, the aim of the study was to examine the features of cognitive control (inhibition of automatic response) and the general level of cognitive functioning in a Russianspeaking sample of alcohol-dependent individuals (AD) using quantitative assessment methods. Materials and Methods. 111 individuals diagnosed with alcohol dependence (F10.30) and 27 healthy participants were examined by using the Brief Assessment of Cognitive Functioning in Affective Disorders Battery (BAC-A) and additional tests of cognitive control (Stroop test with incongruent stimuli, Stroop test with alcohol-associated stimuli). The statistical methods were U-Mann-Whitney test, Spearman correlation coefficient, two-stage least squares regression. Results. In the AD group the indices of cognitive functioning were significantly lower in all parameters except for the subtests of verbal memory and digit sequence (p<0,05). The model of the relationship between the parameters of general cognitive functioning and cognitive control reveals that the index of incongruence to alcohol-related stimuli was a significant predictor of sampe affiliation. Discussion. The obtained results may indicate the presence of impairments of speed of mental processes, planning , verbal fluency and response inhibition function in the group of individuals with AD. In the studied group, the automatic response inhibition function mediates the general cognitive functioning only within the relevant contextual stimuli.